35 Effect of feeding 60% dried corn distillers grains plus solubles or the equivalent sulfur on performance, hormone concentrations, and glutathione peroxidase activity in yearling Angus bulls. (30th November 2020) - Kassetas, Cierrah J; Caton, Joel S; Kirsch, James D; Dorsam, Sheri T; McCarthy, Kacie L; Crouse, Matthew; Neville, Bryan; Sedivec, Kevin K; Dahlen, Carl R
Abstract: The objectives were to investigate the effects of feeding 60% dried corn distillers grains plus solubles (DCD) or equivalent sulfur as calcium sulfate (CaSO4 ) on performance, hormone concentrations, and glutathione peroxidase (GPx ) activity in yearling bulls. Thirty-six half-sibling Angus bulls [256 ± 8 d; initial BW = 320 ± 2 kg] were assigned one of three treatments: 1) corn-based diet containing 60% concentrate (CON; S = 0.18%; n = 12); 2) diet containing 60% DCD as a replacement for corn (DDGS; S = 0.53% DM; n = 12); 3) CON diet + equivalent sulfur of the DDGS diet added as CaSO4 (SULF; S = 0.51%; n = 12). Bulls were fed in Calan gates to target an average daily gain (ADG) of 1.6 kg/d. Data were analyzed as repeated measures using PROC MIXED in SAS. Blood and semen samples were collected on d 0, 56, and 112 then evaluated for concentrations of testosterone, thyroxine, triiodothyronine in serum, and GPx activity in seminal plasma. By design, no differences (P ³ 0.14) were observed among treatments for final BW, ADG or dry matter intake. However, DDGS tended (P = 0.07) to have reduced gain: feed when compared with CON, whereas SULF was intermediate. No differences (P ³ 0.13) were observed among treatments for serum concentrations of testosterone and thyroxine; however, DDGS had reduced (P = 0.009) triiodothyronine concentrations compared with CON and SULF. A treatment ′ d interaction (P = 0.03) was observed for seminal plasma GPx . On d 56, GPx activity was greater (P = 0.03) for DDGS compared with CON, whereas SULF was intermediate, but on d 112, DDGS had greater (P £ 0.02) GPx activity compared with CON and SULF. Therefore, alterations in triiodothyronine concentrations and GPx activity among treatments indicates that DDGS may influence characteristics of semen quality.